Video Profil Nagari Dalam Rangka Penunjang Informasi Data Nagari Koto Tangah Kecamatan Tilatang Kamang - Wahyudi, Ade santika; Jannah, Rodatul; Septiani, Annisa; Putri Anjani, Ayu Anandika; Andres, Fran Serano (Universitas Negeri Padang, 2024)
This research aims to find out the nagari profile video can support data information from the assets of Nagari Koto Tangah, Tilatang Kamang District. The method used in this article is a qualitative research method by describing according to the data obtained. The data used in this research consists of 2 data, namely sources and data from the Medium Term Development Plan (RPJM) Nagari Koto Tangah. Meanwhile, the data used in taking video profiles from (RPJM) and observations made by the team. The result of this research is the nagari profile video can support data information on nagari koto tangah, Tilatang Kamang District